The Development of Islamic Educational Philosophy from Classical to Modern Times - Fitriani Fitriani; Shofiatun Aslamatun Sa’diyah; Nurul Mubin (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study explores the evolution of Islamic educational thought from the classical to the modern era, examining the changing concepts and insights derived from the Qur'an and Hadith as well as the impact of Greek philosophy as incorporated by figures such as Al-Kindi, Al-Farabi, and Ibn Sina. The core of this study is how Islamic educational philosophy evolved from a classical perspective that emphasized the formation of faithful and knowledgeable individuals, to modern thought that embraces contemporary knowledge as well as Islamic values. This article also explores the role of Islamic educational philosophy in addressing current educational challenges with a holistic approach, integrating the spiritual, intellectual, and social dimensions in the learning process. This article highlights the characteristics of Islamic learning in two eras, ancient and modern, and examines key shifts in this history. At that time, Islamic studies were based on the teachings of the Qur'an and Hadith as their primary roots. However, today, there are adjustments to accommodate the complex and dynamic needs of the public. By examining the characteristics of Islamic learning from a historical perspective, this paper hopes to help people understand how Islamic studies have changed over time, and how they have influenced the minds and souls of Muslims.